Bigger than tiny, smaller than average - Koones, Sheri, 1949- (Gibbs Smith, 2022)
Smaller, more environmentally-friendly houses seem to be the wave of the future. As people chose to move out of cities, finances and life style will limit the size of the houses these new home owners will choose. One or both people in the home may have lost their job or the jobs may not be as secure as they were before the pandemic. Even with a future vaccine, people are aware that social distancing situations can occur again and they want to be prepared.